HUBUNGAN FUNGSI KELOMPOK WANITA TANI TERHADAP KINERJA USAHATANI JAHE DI DESA ULUSENA KECAMATAN MORAMO KABUPATEN KONAWE SELATAN - Ramadhan, Ramadhan; Hamzah, Awaluddin; Arfiani, Arfiani (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
Despite the high economic potential and increasing demand for ginger, the performance of ginger farming in Ulusena Village has not reached optimal levels. This is due to a decline in national production, challenges in cultivation, and the suboptimal functioning of the Women Farmers Group (KWT). The objective of this study is to ascertain the correlation between the operational effectiveness of the women farmers' collective and the agricultural performance of the ginger farming enterprise in Ulusena Village, Moramo District, South Konawe Regency. The research population consisted of 15 ginger farmers who were members of the Ulusena Village women farmers group. The research sample consisted of 15 individuals who utilized the census method. The collection of research data entailed the implementation of survey techniques, encompassing the administration of questionnaires, the conduction of interviews, and the review of documentation. The research variables were the function of farmer groups and farming performance. The collected data was then subjected to analysis using descriptive methods. The findings indicated that the Women Farmers Group, comprising learning classes, cooperation, and production units, exhibited commendable implementation among the female farmers in Ulusena Village, Moramo District, South Konawe Regency. The performance of ginger farming, which was measured by product quality, yield, and harvest timing, was also in the good category. Subsequent analysis indicated a positive and significant relationship between the functions of the women farmers' group and enhanced agricultural performance. These findings suggest a direct correlation between the efficacy of group functions and the level of achievement in ginger farming. The results of this study underscore the significance of fortifying the institutional capacity of women farmers' groups in pursuit of enhancing productivity and sustainability in community-based agribusiness enterprises.